2008
DOI: 10.1179/135100008x259259
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 activity in patients with hyperemesis gravidarum

Abstract: There is increasing evidence that oxidative stress may play a role in the pathophysiology of hyperemesis gravidarum. Serum paraoxonase-1 (PON-1) is a high density lipoprotein (HDL)-associated enzyme that prevents oxidative modification of low density lipoprotein. The aim of the study was to measure the serum levels of PON-1 activity in women with hyperemesis gravidarum. Thirty-four women with hyperemesis gravidarum and 31 healthy pregnant women were enrolled in the study. Serum PON-1 activity was measured spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…Based on their results, Engin-Ustun et al concluded that the presence of increased CRP levels in women with HG could contribute to the pathophysiological mechanism of HG, thus showing signs of the inflammatory process were present. Their finding was supported by study of Verit et al (21). Another study has shown that interleukin-6 (IL-6), which is a cytokine produced primarily by activated monocyte/macrophages and T lymphocytes and involved in inflammation and immune responses, levels are increased in pregnant women with HG in the first trimester (20).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Based on their results, Engin-Ustun et al concluded that the presence of increased CRP levels in women with HG could contribute to the pathophysiological mechanism of HG, thus showing signs of the inflammatory process were present. Their finding was supported by study of Verit et al (21). Another study has shown that interleukin-6 (IL-6), which is a cytokine produced primarily by activated monocyte/macrophages and T lymphocytes and involved in inflammation and immune responses, levels are increased in pregnant women with HG in the first trimester (20).…”
Section: Discussionsupporting
confidence: 73%
“…Studies have shown that NLR, PLR, and RDW values are highly associated with the prognosis of diseases related to inflammation (16)(17)(18)(19). The studies investigating the relationship between inflammation and HG are primarily focused on the inflammatory markers in the first trimester as HG predominantly occurs in this period (20,21). However, it is unclear whether the high inflammatory markers in patients with HG cause the disease or they are the product of HG.…”
Section: Introductionmentioning
confidence: 99%
“…A Danish study found a statistically significant association between HG and autoimmune diseases in general and in particular between HG and Sjögren's syndrome, Graves’ disease, rheumatoid arthritis, pernicious anaemia, coeliac disease, Crohn's disease, ulcerative colitis and psoriasis 23. Previous research has also found increased inflammatory markers in women with HG compared with healthy pregnancies 46, 47, 48, 49. Given that several of these conditions associated with HG also are associated with increased risk of CVD, we explored whether HG and CVD‐related mortality might be related.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of high-density lipoprotein (HDL) has been received in HG. 15,16 Thus, Paraoxonase-1 which is a HDLassociated antioxidant enzyme was found low in patients with HG. 15,16 Otherwise lipid peroxidation markers, such as malondialdehyde and lipid hydroperoxide levels, were obtained high in HG.…”
Section: Introductionmentioning
confidence: 96%
“…15,16 Thus, Paraoxonase-1 which is a HDLassociated antioxidant enzyme was found low in patients with HG. 15,16 Otherwise lipid peroxidation markers, such as malondialdehyde and lipid hydroperoxide levels, were obtained high in HG. 13,16 Protein oxidation by the reactive derivatives leads to nitration of aromatic amino acids, oxidation of thiol groups and formation of advanced oxidation protein products and transformation of some amino-acid residues to the carbonyl derivatives.…”
Section: Introductionmentioning
confidence: 96%